2016
DOI: 10.2340/00015555-2301
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Single Nucleotide Polymorphism in a Late Cornified Envelope-like Proline-rich 1 Gene (LELP1) with Atopic Dermatitis

Abstract: There is some evidence that genes involved in the pathogenesis of atopic dermatitis, in addition to the filaggrin (FLG) gene, may be located at chromosome region 1q21. The aim of this study was to examine the association of single nucleotide polymorphisms in the region of the late cornified envelope-like proline-rich 1 (LELP1), hornerin (HRNR) and FLG genes with the course and risk of atopic dermatitis. Single nucleotide polymorphisms and mutations were genotyped by PCR restriction fragment length polymorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 35 publications
1
10
0
1
Order By: Relevance
“…Our study has revealed decreased mRNA expression of FLG, FLG2, LOR, CRNN and SPRR3v1 concomitant with increased LELP1, RPTN, HRNR and SPRR1Av1 mRNA levels in AD compared to healthy controls, which is in line with previous findings [15][16][17][21][22][23][24]. Moreover, the majority of examined CE proteins were decreased in comparison to healthy skin, which confirms that pathological changes also occur in nonlesional AD skin.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study has revealed decreased mRNA expression of FLG, FLG2, LOR, CRNN and SPRR3v1 concomitant with increased LELP1, RPTN, HRNR and SPRR1Av1 mRNA levels in AD compared to healthy controls, which is in line with previous findings [15][16][17][21][22][23][24]. Moreover, the majority of examined CE proteins were decreased in comparison to healthy skin, which confirms that pathological changes also occur in nonlesional AD skin.…”
Section: Discussionsupporting
confidence: 92%
“…Factors such as cornified envelope proteins that contribute to skin barrier dysfunction have been extensively studied, and their role in AD skin barrier defects has been proven [15][16][17][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sharma et al (29) reported significant association of LELP1 rs7534334 with serum IgE levels in patients with atopic asthma (29). Our previous study showed that CC genotype and C-allele of LELP1 rs7534334 were associated with serum IgE levels, severity of AD and concomitant asthma (30). In the present investigation the authors noted an inverse correlation of LELP1 protein level in non-lesional AD skin with serum IgE level, and a positive correlation with severity of disease and pruritus, but these relationships lacked statistical significance, probably owing to the low number of cases examined.…”
Section: Discussionmentioning
confidence: 88%
“…Beside IL - 4, IL - 13, IL - 4RA, IL13RA1, IL - 13RA2 and STAT6 , newly tested genes in this category are thymic stromal lymphopoietin (TSLP), its receptors IL - 7R and TSLPR [ 14 ], and IL - 31 [ 15 ]. In the skin barrier gene category, LAMA3 [ 16 ], TMEM79 , filaggrin - 2(FLG2) [ 17 ] and Late Cornified Envelope - like Proline - rich 1 (LELP1) [ 18 ] were identified to be associated with AD. The vitamin D signaling pathway is a novel pathway that has been explored in AD.…”
Section: Resultsmentioning
confidence: 99%